The inhibition of NCS-1 binding to Ric8a rescues fragile X syndrome mice model phenotypes - Cogram, Patricia; Fernández-Beltrán, Luis C.; Casarejos, María José; Sánchez-Yepes, Sonia; Rodríguez-Martín, Eulalia; García-Rubia, Alfonso; Sánchez-Barrena, María José; Gil, Carmen; Martínez, Ana; Mansilla, Alicia (Frontiers in Neuroscience, 2022)
Fragile X syndrome (FXS) is caused by loss of function of the Fragile X Mental Retardation Protein (FMRP). FXS is the leading monogenic cause of intellectual disability and autism. Although it is produced by the failure of a single gene, due to the FMRP function as an RNA binding protein, a large number of genes are secondarily affected. All these genes represent hundreds of potential targets and different mechanisms that account for the multiple pathological features and consequently, the search of effective treatments is hampered. In this scenario, it seems advisable to reorient therapies towards more general approaches. The neuronal calcium sensor NCS-1, through its interaction with the guanine exchange factor Ric8a, regulates the number of synapses and the probability of neurotransmitter release, two neuronal features that are altered in FXS and other neurodevelopmental disorders. Inhibitors of the NCS1/Ric8a complex have been shown effective in recovering the number of abnormally high synapse number, as well as in improving associative learning in FMRP-mutant flies. Here we demonstrate that an NCS-1/Ric8a inhibitor, the phenothiazine FD44, has strong inhibition ability in situ and has an adequate bioavailability in the mouse brain. More importantly, FD44 treatment in two different FXS model mice, results in a recovery of the well-known FXS phenotypes, such as hyperactivity, associative learning, aggression behavior, stereotypy or impaired social approach. It has been suggested that dopamine may play a relevant role in these behaviors and in neurodevelopmental disorders in general. We have measured dopamine and its metabolites in different brain regions, finding a higher metabolic rate in limbic area, which was also recovered by FD44 treatment. Therefore, in addition to confirm the NCS-1/Ric8a complex as an excellent therapeutic target, we demonstrate the rescue effect of its inhibitor on the cognitive and autistic FXS mice behaviors and show dopamine metabolism as a FXS biochemical disease marker.